Assessment of the current status and effectiveness of area-based conservation measures banning trawling activities in the Adriatic Sea - Ferrà, Carmen; Scarcella, Giuseppe (Frontiers in Marine Science, 2023)
The marine environment is highly stressed by anthropogenic pressures, among which fisheries, and in particular bottom trawling, are one of the main sources of impact. Area-based conservation measures can help conserve and restore ecosystems and population structures and therefore constitute a key tool to the achievement of the 14th Sustainable Development Goal, preservation of the ocean. The purpose of this paper is to provide an assessment of the compliance of area-based conservation measures. The Adriatic Sea has been selected as a case study area, as one of the most intensively trawled areas in the world where different countries share its resources and consequently different management strategies are put in place. We present a review of the marine managed areas established in the Adriatic Sea in 2019, providing information on their characteristics, temporal variabilities, and scopes. Through the processing of Automatic Identification System (AIS) data, the monthly bottom fishing activity performed within each area was inferred and the intensity was assessed. Thus, the effectiveness of trawling bans was evaluated. We demonstrated that full respect of the prohibition was effective in 73% of the areas, while trawling activity was recorded with different intensities in 149 out of 549 managed areas.